Research trend in the development of macroporous ceramic components by pore forming additives from natural organic matters: a short review - Dele-Afolabi, Temitope Theophilus; Mohamed Ariff, Azmah Hanim; Mazlan, Norkhairunnisa; Sobri, Shafreeza; Calin, Recep (Elsevier, 2017)
Macroporous ceramics with tailored porosity offer a great deal of advantage in wide-ranging industrial applications including fluid filtration, thermal insulation and lately, waste water treatment. To a large extent, attempts by researchers in enhancing the development of ample homogenous porous ceramics through the exploitation of state of the art processing technologies have thus far been successful. However, these technologies are capital intensive hence making room for more exploration in finding affordable alternatives. With the growing recognition of low cost sacrificial fugitives processing route for developing porous ceramic materials, pore forming agents from natural organic matters have been one of the most sought after materials for imbuing pores within ceramic matrices. This review intends to document the progress made thus far in the development of porous ceramic systems with natural organic matter inclusion. The article covers critical evaluation and comprehensive comparison of the fabrication routes and the physical properties of porous ceramics processed with varying natural organic matters.